Source rock potential, crude oil characteristics and oil-to-source rock correlation in a Central Paratethys sub-basin, the Hungarian Palaeogene Basin (Pannonian basin). (May 2021) - Körmös, Sándor; Sachsenhofer, Reinhard F.; Bechtel, Achim; Radovics, Balázs Géza; Milota, Katalin; Schubert, Félix
Abstract: Eocene and Lower Oligocene rocks are potential source rocks for crude oil accumulations in the Hungarian Palaeogene Basin. To enhance the understanding of the hydrocarbon system, this study (i) assesses the petroleum potential of Palaeogene formations, (ii) characterises the source rock facies of the accumulated oils, and (iii) provides an oil-to-source correlation. Rock-Eval data of samples from three boreholes (W–1, W–9 and W–12) show that most Palaeogene formations are mature at depths exceeding 2.1–2.5 km. The coal-bearing Kosd Formation includes good to excellent gas- (and oil-) prone source rocks. The overlying Buda Marl Formation is typically organic matter-lean but contains oil-prone rocks with up to 2.3 wt% TOC and a fair petroleum potential in borehole W–9. The Tard Clay Formation in W–12 reaches up to 1.9 wt% TOC and shows HI values up to 440 mg HC/g TOC, characterising the deposits as good petroleum source rocks. Based on low TOC contents, the Kiscell Clay Formation is not considered a source rock. Molecular parameters of 12 crude oil samples indicate a shaly source rock deposited in a marine/brackish environment. Salinity stratification, causing the development of oxygen-depleted conditions, is likely. The organic matter is dominated by aquatic biomass, including algae, dinoflagellates and chemoautotrophic bacteria. Minor angiosperm-dominated organic matter was transported into the basin from the shoreline. Specific V-shaped compound-specific carbon isotope patterns of n -alkanes observed in crude oils and extracts from the Tard Clay prove the dominant source rock. Minor differences between biomarker ratios are related to vertical and lateral facies variations within the Tard Clay Formation. The accumulated oils are slightly more mature than the Tard Clay in borehole W–12. Highlights: Eocene and Oligocene hydrocarbon generating sources in Hungarian Palaeogene Basin. Molecular composition of accumulated crude oils indicates a shaly source rock. Compound-specific carbon isotope determines the dominant source as Tard Clays. V-shape isotope pattern is caused by chemoautotrophic bacterial activity. Contributing source of the Buda Marls is assumable.